The Patterned and Emergent Boundaries of Wilderness Beings: Ponderings on the Creature at the Edge of the Woods - Perry, Donna (Humanimalia, 2016)
This paper explores the permeable boundaries between humans and free-living animals through interweaving the author’s experience with a New England coyote and the cognitional philosophy of Bernard Lonergan. Human knowledge of wildlife emerges within patterned and variable ecological experiences. These emergent encounters are mutually created with both human and creature as knowers of one another. The paper suggests that the variability within human encounters with wild creatures provides a limitation that can serve as an intellectual and moral good. Such encounters call forth human responsibility for ethical decision-making in human-animal relations.